Automatic Identification of Slope Active Deformation Areas in the Zhouqu Region of China With DS-InSAR Results - Wang, Yuanjian; Cui, Ximin; Che, Yuhang; Li, Peixian; Jiang, Yue; Peng, Xiaozhan (Frontiers in Environmental Science, 2022)
Zhouqu has narrow terrain, steep mountains on both sides of Bailong River. It is one of the most serious landslide disasters area in China for the fracture development rock and complex geological codditions. To identify the Slope Active Deformation Areas (SADA) in the region accurately, the Distributed Scatter Interferometric Synthetic Aperture Radar (DS-InSAR) technique was used based on process of the sentinel ascending and descending orbit data.Deformation results of the region from January 2019 to February 2021 were obtained. A new method for automatically identifying SADA while accounting for radar geometric distortion was established to quickly and efficiently identify SADA from the large-scale deformation results in the region. The SADA identified by this method can eliminate the region affected by geometric distortion.62 SADA including 12 in the upstream and 50 in the downstream of Zhouqu County were identified based on the method. Compare with 12 typical landslide areas in the study area, 9 typical landslides match with the detected SADA. The SADA are mainly concentrated in the section from the downstream of Zhouqu County to Lianghekou, and statistical analysis showed that the vegetation coverage and topographic slope angle are two main reasons for this difference. At the same time, the analysis of the typical landslide time-series deformation reveals that the slope deformation activity mainly at rain season.It has high correlation with precipitation. These results of the study provided an important reference for geological disaster prevention in the Zhouqu region.